MENGURAI GAGASAN NEGARA PASCAKOLONIAL: KONTEKSTUALISASI INDONESIA SEBAGAI NEGARA DUNIA KETIGA - Wasisto Raharjo Jati (Kedeputian Bidang Ilmu Sosial dan Kemanusiaan (IPSK-LIPI), 2013)
This article discusses the idea of the postcolonial state in Indonesia. The establishment of the postcolonial state is derived from three perspectives; Marxism, structuralism, and postcolonialism. The idea of postcolonial countries focuses on the premise of over-developed countries and relative autonomy. The context of the relative autonomy of the state itself is interpreted as rivalry in state-society relations for gaining political influence. It was then created the patron-client relation and patronage political economy. In the case of Indonesia, the character of the postcolonial state manifests itself in the form of patrimonialism and the dominance of the state in the public sphere. Reorganization of the old elite to a democratic system indicates linearity values and norms of colonialism in the new system of government.Keywords: Postcolonial, Indonesia, Overdeveloped, Autonomy, Patrimonialism